Supplier selection criteria at Terex Jaques (International) Sdn Bhd / Syaza Ibrahim - Ibrahim, Syaza (2011)
Supplier selection is the strategy adopted by the manufacturer, to evaluate and select suppliers, which fulfills the requirements of the manufacturer. This case study analyzes the main criteria of potential supplier for Terex Jaques (International) Sdn Bhd. Those criteria are quality, delivery performance and cost. This case study first will identify as many as possible factor for each elements, then the researcher will select the major factor for each elements and conduct research to support each factor.